Evaluation of the Application of E-invoice 3.0 at KPP Pratama Jakarta Mampang Prapatan - Grace Talenta Hutagalung; Dwi Martani (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to evaluate the application of e-invoice 3.0 in minimizing the existence of fictitious invoices and their relation to taxpayer compliance based on the perceptions of taxpayers, regulators, and tax consultants. This study uses qualitative and descriptive analysis based on the results of interviews. These respondents were determined purposively. This study uses the Theory Acceptance Model (TAM), the Delone and McLean success model, and Tax Compliance. The results of this study conclude that the application of e-invoicing 3.0 provides the benefits and information needed, increases efficiency, is easy to use, provides convenience and actual processes, system quality, information quality, and good service quality, gives satisfaction to taxpayers (WP)/taxable entrepreneur (PKP), and provide net benefits related to time saving and cost saving for taxpayers. Taxpayers also view that e-invoice 3.0 which has a prepopulated data feature provides convenience for WP/PKP in carrying out VAT tax obligations contributing to tax compliance. The regulator views that e-invoice 3.0 is an effort to minimize fictitious invoices. Ease of use of e-invoice 3.0 leads to tax compliance. In addition, the tax consultant views that e-invoice 3.0 can minimize the existence of fictitious invoices but does not have a significant effect on tax compliance when compared to the previous version. Tax compliance still depends on the individual Taxpayer.